The pattern and outcome of acute severe colitis. - Dinesen, L; Walsh, A; Protic, M; Heap, G; Cummings, F; Warren, B; George, B; Mortensen, N; Travis, S (2010)
BACKGROUND: The prognosis of acute severe ulcerative colitis (ASC) influences therapeutic decisions, but data on prevalence or long-term outcome are few. METHODS: A systematic review of all patients with UC diagnosed in Oxford was performed to assess the prevalence of ASC defined by Truelove and Witts' (TW) criteria and determine whether outcome is related to disease activity on admission, likelihood of recurrence and long-term prognosis. RESULTS: 750 patients (median follow up 12.7 yr, range 0-648 mo) met inclusion criteria out of a total cohort of 1853 patients. 24.8% (186/750) had at least one admission for ASC (294 admissions in 186 patients). Overall, 12% (93/750) had a colectomy, compared to 39.8% (74/186) of patients with one or more episodes of ASC (p<0.0001) and 3.4% (19/564) in those with no admission. The colectomy rate on first admission (37/186, 19.9%) was lower than on the second or subsequent admissions (OR 2.35, 95% CI 1.33-4.14, p=0.003), being 29.0%, 36.6%, 38.2% after two, three, or subsequent episodes respectively. It was 8.5% (11/129) if patients had one TW criterion in addition to ≥6 bloody bowel motions/day, compared to 31% (29/94) if two additional criteria were present and 48% (34/71) if three or more additional criteria were present (p=1.4 × 10⁻⁵; OR 4.35, 95% CI 2.20-8.56 one criterion vs two or more). CONCLUSIONS: A quarter of all patients with ulcerative colitis experience at least one episode of ASC; 20% come to colectomy on first admission, but 40% after two admissions. The likelihood of colectomy is related to biological severity on admission.